Re-certification of respiratory professionals: current practice and the future – educational forum report. Issue 2 (June 2017) - Sehlbach, Carolin; Thomson, Carey; Bennett, Jonathan; Perez de Llano, Luis; Smeenk, Frank; Yokoyama, Akihito; Horváth, Ildikó; Driessen, Erik; Rohde, Gernot
To create an overview on re-certification procedures across the globe, the European Respiratory Society (ERS) organised an educational forum on "Re-certification: current practice and the future" during the 2016 International Congress in London, UK. During this educational forum, the importance of re-certification and international procedures were discussed. Panellists from Japan, the Netherlands, Spain, the UK and the USA presented their respective national re-certification systems. Re-certification of respiratory professionals: a report of an @ERStalk education forum held at #ERSLDN16 http://ow.ly/pUKY30bzcrK